Surface plasmon resonance sensors using reduced graphene oxide-maghemite composite material for plumbum ion detection - Alwahib, Ali Abdulkhaleq Abdulhadi (2017)
As industries rapidly expand to meet the demands of massive dynamic development around the globe, plumbum contamination persists to be among the unsettled environmental issues we have today. The exposure to plumbum is known to cause severe systemic disease even at very low concentrations. The fears from close of Pb2+ sources such as plumbing components to clinical applications and healthy environment are the motivating for developing sensors. Over the past few years, researchers have shown enormous interest in surface plasmon resonance (SPR) based sensors due to its sensitivity and fast response for chemical, biological and environmental sensing applications. The attached nanocomposite-sensing layer to a plasmonic material has created vast integration for sensitivity and selectivity enhancement in detection of heavy metals. This research work focuses on plumbum (Pb2+) ion detection using SPR sensor have a new nanocomposite called reduced graphene-maghemite (rGO/γ-Fe2O3) as a sensing layer. The main aspects of the study are the sensing potentiality of rGO/γ-Fe2O3 in prism based SPR sensor technique, protect the rGO/γ-Fe2O3 from degradation in water environment and finally detect plumbum in water using rGO/γ-Fe2O3 at sub ppb detection limits. Preliminary studies of the sensing layer when tested with hydrocarbon vapor show that it is sensitive towards acetone as compared to ethanol, propanol and methanol, which highlights the first demonstration of rGO/γ-Fe2O3 nanomaterial in optical sensing applications. For heavy metal ion detection, its main challenge is the erosion of graphene-based nanomaterial when the layer interacts with aqueous analyte. Therefore, a special material matrix is required to enhance the adhesiveness of rGO/γ-Fe2O3 to the gold (Au) layer on SPR and the combination of Au-rGO/γ-Fe2O3 sensing layer and 1-Ethyl- 3-(3-dimethylaminopropyl)carbodiimide/ N-Hydroxysuccinimide/ (EDC/NHS) as a protection layer is used in the sensor structure. The optimized thicknesses of Au, rGO/γ-Fe2O3 and EDC/NHS are 41, 8.75 and 4 nm, respectively and its limit of detection for Pb2+ ions is 0.001 ppm in static water conditions. The limit of detection is further enhanced to 0.3 ppb by adopting the water circulation method. Selectivity of Pb2+ ions is greatly enhanced, by replacing EDC/NHS with polyvinylchloride (PVC). This work highlights the advantages of rGO/γ-Fe2O3 nanocomposite as the sensing layer on an SPR based sensor for the detection of Pb2+ ions in water. Its sensing performance has shown great potential in matching the need for a robust, cheap, sensitive and selective sensing method to detect heavy metals and help curb the environmental problem. The quantitative research findings are 1.1-degree angle shift in 10% concentration vapor acetone, EDC/NHS enhanced the sensing layer to work under water circulation for 50 experiments and detection of plumbum ions in water at concentration 0.3 ppb.